Efficacy and safety of radiofrequency in the treatment of hidradenitis suppurativa; a systematic review - Nilforoushzadeh, Mohammad Ali; Heidari, Nazila; Heidari, Amirhossein; Ghane, Yekta; Hosseini, Seyedayin; Lotfi, Zahra; Jaffary, Fariba; Nobari, Minou Najar; Aghamiri, Zahra Sadat; Nobari, Niloufar Najar (Lasers in medical science, 2024)
Background and aims Hidradenitis suppurativa (HS) is an inflammatory skin disease affecting apocrine gland-bearing sites of the body. Radiofrequency (RF) is a minimally invasive method that acts by minimizing thermal damage to the dermis, resulting in collagen synthesis and scar improvement. We systematically reviewed the efficacy and safety of RF in treating HS. Methods A systematic search was performed up to November 18th, 2023, in PubMed/Medline, Ovid Embase, and Web of Science. Clinical studies with English full texts were included. The National Institute of Health (NIH) Quality Assessment Tool for clinical trials and Methodological quality and synthesis of case series and case reports by Murad et al. were utilized for critical appraisal. Results Out of 55 identified studies, 11 met our inclusion criteria with 167 subjects who underwent RF therapy alone or combined with an intense pulsed laser (IPL), known as LAight®. LAight® significantly improved clinical outcomes in mild-to-moderate HS patients based on the Dermatology Life Quality Index (DLQI), International Hidradenitis Suppurativa Score System (IHS4), Pain-Numerical Rating Scale (NRS), and Hidradenitis Suppurativa Clinical Response (HiSCR). Moreover, RF therapy alone significantly alleviated the clinical manifestations in patients with mild-to-moderate HS. Additionally, fractional microneedling RF significantly decreased HS-associated inflammatory markers. RF was found to be safe with limited adverse events. However, in moderate-to-severe HS, RF has failed to yield satisfactory results. Conclusion RF is a safe energy-based method with promising outcomes, especially for long-term application in mild-to-moderate HS. In moderate-to-severe cases, RF should be combined with a systemic medication for further beneficial impacts.